Lull pgm system: A suitable technique to improve the regenerative potential of autologous fat grafting. Issue 4 (11th October 2017) - Morselli, Paolo G.; Giorgini, Federico A.; Pazzini, Claudia; Muscari, Claudio
Abstract: Autologous fat grafting and methods of purification of harvested tissue have become one of the most current themes in regenerative medicine. The aim of this study was to evaluate the in vitro regenerative potential of abdomen lipoaspirates subjected to a combined washing‐decantation purifying procedure, the Lull pgm System (Lull). Blood cells and stromal‐vascular fraction (SVF) cells contained in the aspirates were investigated and compared with those obtained through more conventional fat‐processing methods, that is, the decantation and Coleman's centrifugation techniques. The lowest number of erythrocytes, which are proinflammatory cells, was observed in the Lull samples, corresponding to about 50% of those isolated by decantation and centrifugation. The highest amount of SVF cells were isolated from the Lull samples whose number of colony forming units, representative of the amount of adipose‐derived stem cells (ADSCs), was about fourfold and sixfold higher than in the decantation and centrifugation samples, respectively. Adipocyte and osteoblast commitment of SVF cells obtained from all the three procedures also confirmed that the subpopulation of ADSCs was actively represented in the processed aspirates. Moreover, the growth rate of the SVF cells was more accentuated in the samples obtained from decantation and Lull than centrifugation. In conclusion, Lull seems to be the best processing technique for adipose tissue graft with respect to decantation and centrifugation, because it clears more efficiently the fat from proinflammatory blood cells and provides the greatest number of proliferating SFV cells and ADSCs.